ADSORPTION OF Pb(II), Cd(II), AND Cr(III) FROM AQUEOUS SOLUTION BY POLY-5-ALLYL-CALIX[4]ARENE TETRA CARBOXYLIC ACID - Desi Suci Handayani; Jumina Jumina; Dwi Siswanta; Mustofa Mustofa; Keisuke Ohto; Hidetaka Kawakita (Indonesian Journal of Chemistry, 2011)
The aim research is application of poly-5-allyl-calix[4]arene tetra carboxylic acid as adsorbent of heavy metal cations. Adsorption was carried out towards Pb(II), Cd(II) and Cr(III) ions in batch system. Several variables including pH, contact time and initial concentration of metal ions were determined. The optimum adsorption conditions were achieved at pH 6.0 for Cd(II) and Cr(III), while at pH 5.5 for Pb(II) ions. In addition, the optimum contact time of Pb (II), Cd(II) and Cr(III) ion adsorption were 180 min. The adsorption kinetics of Pb(II), Cd(II) and Cr(III) ions using the calixarene polymer adsorbent followed a pseudo 2nd order kinetics model, with adsorption rate constants of 2x10-2; 5x10-3, and 3.1x10-2 g mole-1 min-1, respectively. Furthermore, the adsorption isotherm of Pb(II) and Cd(II) ions tends to follow the Freundlich isotherm, whereas the adsorption of Cr (III) tends to follow the Langmuir isotherm. The adsorption capacity of Pb(II), Cd(II) and Cr(III) metal ions were 104.04, 61.78 and 228.69 μmole/g, with adsorption energy of 24.87; 21.62 and 31.07 KJ/mole, respectively.